Litho-sedimentological characteristics of Pre-Cenozoic carbonate in Ham Rong field, Northeast of Song Hong basin - Tam, Le Trung; Hoang, Cu Minh; Tuan, Pham Van (Petrovietnam Journal, 2014)
The Ham Rong field (Block 106) was discovered in the Pre-Cenozoic carbonate by the HR-1X and HR-2X wells. Well tests were carried out in both wells with commercial oil flow rates. Four hundred metres of carbonate basement were penetrated by the HR-2X well, and cutting samples and side wall cores were gathered whilst logging and testing were conducted in this well. This paper presents the results of study on the litho-sedimentological characteristics of Pre-Cenozoic carbonate in the Ham Rong field based on the analysis of integrated data gathered from the HR-1X and HR-2x wells. The main results include lithological components, characteristics of depositional environments, secondary alteration activities, carbonate rock classification and reservoir characterisation. The results achieved will be very useful for evaluation of the quality of Pre-Cenozoic fractured carbonate reservoir and for guiding further exploration activities in the northeast of Song Hong Basin.